2020
DOI: 10.3390/agronomy10121955
|View full text |Cite
|
Sign up to set email alerts
|

Growing Medium Type Affects Organic Fertilizer Mineralization and CNPS Microbial Enzyme Activities

Abstract: Managing plant fertilization is a major concern of greenhouse growers to achieve sustainable production with growing media (GM). Organic fertilization is popular but is more difficult to control, since organic compounds need first to be mineralized by microbes. After 7, 14, 28, and 56 days of incubation, we investigated the response of microbial activities and nutrient releases from three frequently used organic fertilizers (horn and two plant-based fertilizers) in three frequently employed GM types (peat, coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 84 publications
2
30
0
Order By: Relevance
“…In contrast, organic constituents (such as coconut fiber or green waste compost) or their mixture contained bacterial ammonia oxidizers and nitrifiers [29]. In any case, among organic growing media, each substrate drove nitrogen mineralization and nitrification after organic fertilization according to its own chemical and biological features: peat was distinguished for a weak nitrification due to its low pH, while bark showed low microbial enzyme activities independently on the added organic fertilizer [30]. In most cases, organic fertilizer types modulated microbial activity of growing media, finding, for example, lower activities and nutrient release with horn meal than with plant-based fertilizers [30].…”
Section: Advantages and Limits Of Soilless Agriculture In The Process Towards Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, organic constituents (such as coconut fiber or green waste compost) or their mixture contained bacterial ammonia oxidizers and nitrifiers [29]. In any case, among organic growing media, each substrate drove nitrogen mineralization and nitrification after organic fertilization according to its own chemical and biological features: peat was distinguished for a weak nitrification due to its low pH, while bark showed low microbial enzyme activities independently on the added organic fertilizer [30]. In most cases, organic fertilizer types modulated microbial activity of growing media, finding, for example, lower activities and nutrient release with horn meal than with plant-based fertilizers [30].…”
Section: Advantages and Limits Of Soilless Agriculture In The Process Towards Sustainabilitymentioning
confidence: 99%
“…In any case, among organic growing media, each substrate drove nitrogen mineralization and nitrification after organic fertilization according to its own chemical and biological features: peat was distinguished for a weak nitrification due to its low pH, while bark showed low microbial enzyme activities independently on the added organic fertilizer [30]. In most cases, organic fertilizer types modulated microbial activity of growing media, finding, for example, lower activities and nutrient release with horn meal than with plant-based fertilizers [30]. It is generally concluded that it is relevant to define an adequate fertilization strategy, made by selected media components and organic fertilizer type, to obtain a known nitrifying community that allows one to predict and control the microbial nitrogen conversion and delivery to plants [29,30].…”
Section: Advantages and Limits Of Soilless Agriculture In The Process Towards Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other organic fertilizers, MBM is a slow-release fertilizer containing N and P that are unavailable for uptake by plants [36]. In soil, they are converted to plant-available mineral forms via biophysicochemical processes [33,37]. The rate of mineralization of organic compounds in soil depends on its temperature, physical properties (moisture content, structure, and granulometric composition), chemical properties (composition of the introduced organic matter), the C/N ratio, and the activity of soil-dwelling microorganisms [38].…”
Section: Introductionmentioning
confidence: 99%
“…However, microflora are absent in soilless systems. Therefore, mineralization of OF sources in soilless systems are affected, and thus the bioavailability of nutrients to the plant is also reduced Paillat et al, 2020). For this reason, use of OFs that do not require further mineralization is important for optimizing organic vegetable production under soilless greenhouse conditions (Bi et al, 2010).…”
mentioning
confidence: 99%